2020
DOI: 10.1007/s00508-020-01759-x
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective comparison between influenza and COVID-19-associated ARDS in a Croatian tertiary care center

Abstract: Background Since the beginning of the Corona virus disease 2019 (COVID-19) pandemic the new Severe acute respiratory syndrome coronoavirus 2 (SARS-CoV-2) virus has been repeatedly compared to the influenza virus; however, the comparison of invasively mechanically ventilated patients with acute respiratory distress syndrome (ARDS) caused by these viruses is very scarce. The purpose of this study was to compare clinical course and laboratory parameters between the most severely ill flu and COVID 19 patients trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 13 publications
2
14
0
Order By: Relevance
“…Three prospective investigations, 82 retrospective observational analyses and 49 case reports/series of COVID-19 patients on ECMO for a total 134 studies (references to the 134 studies in Supplemental Appendix 1), were selected for the systematic review and metaanalysis of single proportions or single means, and six [23][24][25][26][27][28] of them were eligible for the comparative meta-analysis of COVID-19 ECMO patients vs influenza ECMO patients.…”
Section: Resultsmentioning
confidence: 99%
“…Three prospective investigations, 82 retrospective observational analyses and 49 case reports/series of COVID-19 patients on ECMO for a total 134 studies (references to the 134 studies in Supplemental Appendix 1), were selected for the systematic review and metaanalysis of single proportions or single means, and six [23][24][25][26][27][28] of them were eligible for the comparative meta-analysis of COVID-19 ECMO patients vs influenza ECMO patients.…”
Section: Resultsmentioning
confidence: 99%
“…Healthcare professionals, researchers and the lay-public have compared COVID-19 and influenza characteristics [ 11 – 13 , 27 ]. In influenza, studies have found a positive relationship between viral load and disease severity [ 28 31 ] but there is conflicting data regarding this relationship in COVID-19 [ 2 , 3 , 5 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Physicians and researchers have compared COVID-19 to influenza [ 11 – 13 ] possibly because of the general public's better understanding of the flu. In addition, there is similarity in structure between coronavirus and influenza [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, we have limited published data from Central-Eastern European ICUs [19][20][21][22] to compare our data to, but the current results on mortality match with those published on the national and international websites, suggesting that mortality of COVID-19 patients in the six countries included in the current analysis was somewhat higher than in our Western European counterparts [6].…”
Section: Mortalitymentioning
confidence: 62%